Preparative thin‐layer chromatographic separation followed by identification of antifungal compound in Cassia laevigata by RP‐HPLC and GC‐MS. (17th July 2013) - Panigrahi, Gatikrushna; Maheshwari, Richa; Vellaikumar, S.; Jayaprakash, S.P.; Kumar, Sandeep; Prabakaran, J.
Abstract BACKGROUND Several species of the genus Cassia are known for their antioxidant, antimicrobial and antidiabetic activities, but some of the lesser‐known Cassia species, e.g. C. renigera, C. biflora and C. laevigata have not been studied for their biological activities. RESULTS Methanol extract of C. laevigata was fractionated by preparative thin‐layer chromatography. The resulting six different fractions were tested against Fusarium oxysporum and Aspergillus niger for their antifungal activity. Due to higher antifungal activity of fraction 1 of C. laevigata, this was further analyzed by reversed‐phase high‐performance liquid chromatography (RP‐HPLC), resulting in distinct separation of one compound at a retention time of 7.2 min with an absorbance of 252 nm. Further, this compound was analyzed by gas chromatography–mass spectrometry (GC‐MS) for its putative structural identification. Mass spectra of this compound resembled the spectra of anthraquinone 1‐carboxylic acid by NIST library search. The genomic‐level expression of chalcone synthase, a key enzyme involved in the biosynthesis of polyketides, was increased in C. laevigata when compared to other Cassia species. CONCLUSIONS This study provides an insight into the higher antifungal activity of C. laevigata, including the identification of anthraquinone 1‐carboxylic acid, which may be responsible for the antifungal activity. © 2013 Society of Chemical Industry